2013
DOI: 10.3844/ajassp.2013.1087.1092
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF <I>MELALEUCA CAJUPUTI</I> AS HEAVY METALS PHYTOREMEDIATOR FOR SEWAGE SLUDGE CONTAMINATED SOIL

Abstract: In 2011, total marine capture landings in Peninsular Malaysia decreased by 3.9% which amounted to 1,373,105 tonnes as compared to 1,428,881 tonnes in 2010. The decline is connected to marine pollution which mainly comes from land based sources. Coastal forests play an important role affecting the marine ecosystem health and need to be conserved as a buffer to minimize pollution input into marine ecosystem. Heath forest, a type of coastal forest that receives less attention compared to mangroves, also has simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…It was observed that Jatropha curcas accumulated significant amounts Zn, Cu and Pb in their parts. Highest concentrations of these heavy metals were recorded in shoot than the root and this might be attributed to its importance in biochemical reactions especially in photosynthesis (Mohd et al,2013). The high concentrations of heavy metals in the shoots may indicate active translocation of these metals from roots to shoots.…”
Section: Physiochemical Parameters Of the Potting Mediamentioning
confidence: 93%
“…It was observed that Jatropha curcas accumulated significant amounts Zn, Cu and Pb in their parts. Highest concentrations of these heavy metals were recorded in shoot than the root and this might be attributed to its importance in biochemical reactions especially in photosynthesis (Mohd et al,2013). The high concentrations of heavy metals in the shoots may indicate active translocation of these metals from roots to shoots.…”
Section: Physiochemical Parameters Of the Potting Mediamentioning
confidence: 93%
“…Gambar 7 dan Gambar 8 tersebut menunjukkan bahwa semua perlakuan mengalami keguguran namun selanjutnya mengalami peningkatan jumlah daun baik secara cepat maupun lambat. Hal ini menunjukkan ketahanan bibit kayu putih yang cukup baik untuk bertahan pada kondisi tercemar air asam tambang sesuai dengan yang disampaikan Mohd et al (2013) bahwa bibit kayu putih dapat bertahan pada lahan yang tergenang dan terkontaminasi bahan berbahaya melalui proses fisiologisnya. Kayu putih mereduksi bahan berbahaya menjadi tidak berbahaya dan mengubahnya dalam bentuk biomassa khususnya biomassa di atas tanah atau pucuk.…”
Section: Air Asam Tambangunclassified
“…Sewage, toxic chemicals from industries, land runoff, large scale oil spills, ocean mining and littering also cause for contamination of seawater [38]. Most sources of marine pollution are land based [39,40], such as windblown debris, industrial / domestic pollutants discharged and potential spillovers from freight/ bulk ocean carriers. Other factors causing marine pollution are direct discharge of industrial waste & sewerage, land run of ship pollution, atmospheric pollution, deep sea mining, acidification, eutrophication, marine fish production, plastic debris [40].…”
Section: Preserving Of Water Resource From Pollutionmentioning
confidence: 99%